Second study on the recurrence risk of isolated esophageal atresia with or without trachea‐esophageal fistula among first‐degree relatives: No evidence for increased risk of recurrence of EA/TEF or for malformations of the VATER/VACTERL association spectrum. Issue 12 (5th December 2013) - Choinitzki, Vera; Zwink, Nadine; Bartels, Enrika; Baudisch, Friederike; Boemers, Thomas M.; Hölscher, Alice; Turial, Salmai; Bachour, Haitham; Heydweiller, Andreas; Kurz, Ralf; Bartmann, Peter; Pauly, Markus; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Esophageal atresia with/without trachea‐esophageal fistula (EA/TEF) denotes a spectrum of severe congenital malformations. The aim of this systematic study was to determine both the recurrence risk for EA/TEF, and the risk for malformations of the VATER/VACTERL association spectrum, in first‐degree relatives of patients with isolated EA/TEF. METHODS A total of 108 unrelated patients with isolated EA/TEF were included. These individuals had 410 first‐degree relatives including 194 siblings. The presence of EA/TEF and malformations of the VATER/VACTERL association spectrum in relatives was systematically assessed. Data from the EUROCAT network were used for comparison. RESULTS None of the first‐degree relatives displayed any form of EA/TEF. In two families, a first‐degree relative presented with malformations from the VATER/VACTERL association spectrum. However, no increase in the risk for malformations of the VATER/VACTERL association spectrum was found compared with the control cohort (p = 0.87). In three families, one more distantly related relative presented with EA/TEF. CONCLUSION In contrast to previous studies, our results suggest a very low recurrence risk for isolated EA/TEF and/or for malformations of the VATER/VACTERL association spectrum among first‐degree relatives. Birth Defects Research (Part A), 97:786–791, 2013. © 2013 Wiley Periodicals, Inc.